Healthy Herbal Teenagers: Reproductive Health Improvement Strategies at SMK Bhakti Asih - Harmatuti, Harmatuti; Aurelia, Putri Yasyfa (CV. Publikasi Indonesia, 2025)
Adolescent reproductive health is one of the important issues in community health development. Low knowledge and unhealthy lifestyles can trigger various problems, such as anemia, dysmenorrhea, and hormonal disorders. The